Oral distribution of Candida species and presence of oral lesions in Brazilian leprosy patients under multidrug therapy - Ferraz de Araujo Navas, Edna Aparecida [UNESP]; Inocencio, Aline Cassia [UNESP]; Almeida, Janete Dias; Back Brito, Graziella Nuernberg [UNESP]; Mota, Adolfo Jose; Cardoso Jorge, Antonio Olavo [UNESP]; Rodrigues Querido, Silvia Maria [UNESP]; Balducci, Ivan [UNESP]; Koga-Ito, Cristiane Yumi [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
Objective:The aim of this study was to evaluate the prevalence of Candida spp. and presence of oral lesions in Brazilian leprosy patients under multidrug therapy (MDT).Methods:Thirty-eight individuals (18 males and 20 females, median age 53 years) clinically and microbiologically diagnosed as leprosy (lepromatous variant), and under MDT for at least 45 days were studied. The control group constituted by 38 healthy individuals (median age 53.5), matched to the test group in relation to age, gender and oral conditions. Oral rinses were collected and the Candida identification was performed by phenotypic tests. The existence of Candida dubliniensis among the isolates was analyzed using a validated multiplex PCR assay. Twenty-nine leprosy patients were examined intra-orally for the presence of lesions. Data were analyzed by z- and Mann-Whitney tests (alpha = 5%).Results:Yeast carriage rate between leprosy patients (65.8%) and controls (47.4%) was similar (P = 0.099), and no significant difference between yeast counts was observed (P = 0.1004). Candida albicans was the most frequently isolated species in both groups. In the leprosy group, Candida tropicalis and Candida parapsilosis were also identified. In the control group, we additionally identified Candida tropicalis, Candida glabrata and Candida kefyr. Candida dubliniensis was not detected. No leprosy-related oral lesion was registered.Conclusion:Within the limits of the study, we concluded that Brazilian leprosy patients under MDT showed similar levels of carriage and Candida species distribution in relation to the controls.
Keywords: Brazil; Candida; diagnosis; leprosy; oral; oral manifestations